Nutrient composition and ameliorative effects of Cocos nucifera products on Alloxan-induced diabetic wistar rats - Benjamin, Amadi; Charity, Ogunka-Nnoka; Peter, Amadi; Miebaka, Ogaji (International Journal of Medicine, 2017)
Using standard methods, this study investigated the ameliorative effects of coconut products during alloxan-induced diabetic conditions. Experimental animals were divided into five groups, group 1 served as normal control rats fed only rat chow and saline, group 2 were dia-betic control rats intraperitoneally treated with 150mg/kg body weight alloxan monohydrate, group 3 were diabetic rats orally treated with 4ml/day of coconut milk, group 4 were diabetic rats orally treated with 4ml/day of coconut water, and group 5 were diabetic rats orally treat-ed with 4ml/day of a mixture of coconut milk and coconut water. The coconut products had high moisture, fats, potassium, magnesium, and sodium contents. Coconut milk exhibited the most effective glucose lowering effect, and on the 21st day. The total cholesterol was com-pletely normalized on treatment with coconut milk after alloxan induced diabetes, while the administration of the mixture of coconut milk and water had a comparable effect to administering only coconut milk on HDL, LDL, and TG. The alloxan-induced derangements on SOD, catalase and GPx were completely normalized after the coconut milk administration, while the mixture of coconut milk and water restored only SOD and GPx, and coconut water, ineffective on most of the antioxidant enzymes. Coconut water was ineffective on the RBC and HB of diabetic rats, while coconut milk and the mixture of coconut milk and water showed the most hemato-ameliorative effect. This study has shown the effectiveness of coconut products in the management of diabetes, with coconut milk the most effective.